2004
DOI: 10.1038/sj.hdy.6800517
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome inheritance in triploid Pacific oyster Crassostrea gigas Thunberg

Abstract: Reproduction and chromosome inheritance in triploid Pacific oyster (Crassostrea gigas Thunberg) were studied in diploid female  triploid male (DT) and reciprocal (TD) crosses. Relative fecundity of triploid females was 13.4% of normal diploids. Cumulative survival from fertilized eggs to spat stage was 0.007% for DT crosses and 0.314% for TD crosses. Chromosome number analysis was conducted on surviving progeny from DT and TD crosses at 1 and 4 years of age. At Year 1, oysters from DT crosses consisted of 15%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 23 publications
0
37
1
Order By: Relevance
“…On the other hand, other studies have shown that the production of fully mature gametes in triploid Pacific oysters is greatly reduced compared to diploids, i.e. between 2 and 13% of diploid female oocyte production (Guo & Allen 1994c, Gong et al 2004.…”
Section: Gonadogenesis In Diploid and Triploid Spatmentioning
confidence: 97%
See 1 more Smart Citation
“…On the other hand, other studies have shown that the production of fully mature gametes in triploid Pacific oysters is greatly reduced compared to diploids, i.e. between 2 and 13% of diploid female oocyte production (Guo & Allen 1994c, Gong et al 2004.…”
Section: Gonadogenesis In Diploid and Triploid Spatmentioning
confidence: 97%
“…Environmental variation probably also contributes to variability of reproductive effort estimators published for triploid Pacific oysters (Allen & Downing 1986, Shpi-gel et al 1992, Guo & Allen 1994c, Gong et al 2004. Further comparative studies of triploid versus diploid performances should be made under different environmental conditions (i.e.…”
Section: Gonadogenesis In Diploid and Triploid Spatmentioning
confidence: 99%
“…Such non-sterile triploid oysters have been named triploid alpha (3nα) oysters, differentiating them from those producing only a few gametes called triploid beta (3nβ) [20]. Interestingly, gametes of triploid oysters can reach functional maturity [23] and when fertilized, can develop into some viable progeny, though the proportion of aneuploids is high [23], [24].…”
Section: Introductionmentioning
confidence: 99%
“…In four isolates studied, we found two dominant karyotype patterns in which the two nuclei differ in one and two chromosomes, respectively. Occurrence of minor karyotype variants in each Giardia isolate conforms to a usual frequency of artifacts of a spreading technique used for chromosome preparations (Gong et al 2004;Rosenbusch 2004). Both statistical evaluation of karyotype distribution and approximately the same rate of variation in the isolates (three noncloned, geographically distinct isolates and the cloned line WB-1B) suggest that also in Giardia, the minor variants represent the artifacts.…”
Section: Karyotypes Of Giardia Nucleimentioning
confidence: 77%